ONLINE CUSTOMER REVIEW DAN KONTEN MARKETING DALAM PLATFORM TIKTOK PADA KEPUTUSAN PEMBELIAN PRODUK - Aba Yayit Al Bustomi,; Henry Yuliamir,; Idah Kusuma Dewi, (Journal of Innovation Research and Knowledge, 2025)
Both marketing information and online customer reviews have a big impact on consumer decision-making. The purpose of this study is to ascertain and investigate the degree to which online customer evaluations and TikTok marketing content influence consumers' product selections. Because this study takes a quantitative approach, data were gathered via questionnaires, literature studies, and observation. One hundred Ungaran respondents made up the study's sample. Two factors related to purchase decisions the marketing content variable and the online customer review variablewere computed in the t-test computation. These two values show that the purchase choice variable is influenced by both of these factors. Additionally, the results of the F test show that the marketing material variable and online customer reviews both simultaneously influence the decisions of product buyers